Is there a motherhood penalty in academia? The gendered effect of children on academic publications - Mark Lutter; Martin Schröder (Max Planck Institute for the Study of Societies, 2019)
Based on data that tracks CV and publication records as well as survey information from sociologists in German academia, we examine the effects of parenthood on the publication output of male and female academics. Results indicate that having children leads to a significant decline in the number of publications by women, while not affecting the number of publications by men. We also find that the gendered effect of children on productivity hardly mitigates differences in publication output between men and women, as women still publish about 20 percent less than men after controlling for the adverse effects of children on productivity. We further find that the gendered effect of childbearing depends partly on prior levels of women's academic achievements, which suggests mechanisms of performance-driven self-selection. Lower-performing women tend to suffer a stronger motherhood penalty, while the publication output of more successful women (who have been granted academic awards) is not reduced through childbirth. The results indicate that women are better at managing the 'double burden' of parenthood and career if external, award-giving committees have bestowed prestige upon them and indicated their potential for a scientific career. Overall, these findings contribute to a better understanding of how to reduce the adverse effect of children on female publication output. – – Auf Basis eines Datensatzes, der Lebenslauf- und Publikationsdaten sowie Informationen aus einem Online-Survey von deutschen Soziologinnen und Soziologen verbindet, untersuchen wir die Auswirkungen von Elternschaft auf den Publikationsoutput von Wissenschaftlern und Wissenschaftlerinnen. Die Ergebnisse zeigen, dass Elternschaft zu einem signifikanten Rückgang der Publikationen bei Frauen, nicht aber bei Männern führt. Ebenso zeigt sich jedoch, dass dieser geschlechtsspezifische Effekt bestehende Publikationsunterschiede zwischen Männern und Frauen kaum beseitigt. Frauen publizieren etwa 20 Prozent weniger als Männer, auch nachdem statistisch kontrolliert wird, dass Kinder die Publikationen von Frauen stärker senken als von Männern. Ferner zeigt sich, dass der negative Kinder-Effekt bei Frauen teilweise durch ihre bisherigen akademischen Errungenschaften erklärt werden kann, was auf Selbstselektionseffekte hinweist. Frauen, die mit akademischen Preisen als aussichtsreiche Kandidatinnen für eine akademische Karriere ausgezeichnet wurden, erleben einen geringeren Rückgang an Publikationen, wenn sie Kinder haben. Insgesamt tragen die Resultate zu einem besseren Verständnis dazu bei, wie die negativen Effekte von Elternschaft auf den Publikationsoutput von Frauen verringert werden könnten.
hdl:21.11116/0000-0003-009A-F
Keywords: 300; academic career; academic publications; children; gender gap; motherhood penalty; Benachteiligung von Müttern; Geschlecht; Kinder; wissenschaftliche Karrieren; wissenschaftliche Publikationen